Prediction of stature from arm-span-An Anthropometric study on 100 Bangladeshi adult Muslim male of Lower socioeconomic status group (Journal of Dhaka National Medical College & Hospital, 2014)
To determine the stature from arm-span may be needed in the older persons whose original stature have already reduced due to aging process or unable to take actual measurement of a person due to curvature of vertebral column abnormality i.e. kyphosis, lordosis and scoliosis or partial loss or total loss of the lower limb or bowing of legs and bent knees. Sometimes it is impossible to take measurement of bed ridden patients. In these cases the original stature of those people can be measured by multiplying the measuring value of the arm-span with the multiplication factor. The multiplication factor can be obtained by making ratio of the stature to the arm-span. This multiplication factor varies from one race to another race, one sex to another sex and one ethnic group to another ethnic group. Therefore the present study was carried out in order to establish a multiplication factor of Bangladeshi adult Muslim male of lower socio-economic status group. The sample subjects were 100 Bangladeshi Muslim males of lower socio-economic status aged between 25 to 30 years. The arm-span along with stature was measured directly from the subject by measuring steel tape. The data were then statistically analyzed by computation to find out its normative value. Comparison was made between measured and estimated stature of the same person by using paired “t” test. In the study the multiplication factor was revealed 0.940 ± 0.038.J. Dhaka National Med. Coll. Hos. 2014;20(01):54-57